Two new species of the genus Apanteles Foerster, 1862 (Hymenoptera: Braconidae: Microgastinae) from Vietnam - Long, Khuat Dang (Academia Journal of Biology, 2014)
Two species belonging to Apanteles merula-group (Nixon, 1965) are described as new to science: Apanteles gialamensis Long K, sp.n. and A. subcamilla Long K, sp.n. 1. Apanteles gialamensis Long K, sp.n. (fig. 1-7) Material: Holotype, ♀Apan.508 (IEBR): VN, Hanoi (Gialam), beans field, 13.IV.2006, K. D. Long; paratypes 3♀ Apan.508a, Apan.508b, 2♂ Apan.508c, Apan.508d (IEBR): locality as holotype; 1♀ Apan.634 (IEBR): VN, Hanoi (Gialam), sweeping, 20.V.2006, K. D. Long. Holotype: ♀, length of body 3.0 mm, of fore wing 3.3 mm, of setose part of ovipositor sheath 1.2mm and of antenna 2.5mm. Head (figs 3, 4): antenna shorter than body (0.8 times as long as body); eyes not convergent below (fig. 4); antennal sockets above middle line of eyes; face width 1.2 times height of eye and 1.3 times length of face and clypeus combined (fig. 4); tentorial pits small, distance between tentorial pits 2.3 times distance from pit to eye margin. Head in dorsal view transverse, width about 2.2 times as long as median length (fig. 3); ocelli rather large in high triangle, anterior tangent of the posterior ocelli not touching the anterior ocellus, distance between posterior ocelli (POL) 2.0 times diameter of posterior ocellus (Od) and 0.8 times distance from posterior ocellus to eye margin (OOL). Face, apex and occiput with dully fine punctures. Mesosoma: in dorsal view, mesoscutum 1.25 times as wide as width of head; mesoscutum finely punctate; scutellum with sparse and shallow punctures. Propodeum almost polished smooth, spiracles above middle line of propodeum (fig. 5). Wings: fore wing 1.1 times as long as body; vein r arising behind middle of pterostigma and vein r longer than vein 2-SR, vein 2-SR thicker than r, veins r and 2-SR weakly angled (fig.1); metacarp very long, 1.15 times as long as pterostigma and 6.2 times as long as its distance from the apex of the radial cell; vein 2-CU1 about 1.4 times as long as vein 1-CU1; vein 1-CU1 equal vein cu-a; hind wing broad with cubitellan cell as long as wide (fig. 2). Legs: hind tibia 0.7 times as long as hind tarsus; inner hind tibial spur 0.53 times as long as hind basitarsus; hind basitarsus about 0.7 times hind tarsus; telotarsus shorter than fourth (4: 5). Metasoma: tergite weakly constricted at the middle and noticely narrowed at apex (fig. 6); length of the first tergite 2.25 times apical width; tergite 1 smooth and with sparse sharp punctures; median field of tergite 2 about 2.7 times median length; tergites 2+3 polished smooth with faint suture. Ovipositor long and abruptly curved down at apex (fig. 7); hypopygium not developed; setose part of ovipositor sheath about 0.4 times body (fig. 7). Colour: body polished black; maxillary palpi white, except first segment dark brown; apical one third of fore tibia and tarsus whitish yellow; middle legs black, whitish yellow basally; middle tarsus whitish yellow; hind legs black; tibial spurs white; wings hyaline with veins and setae almost colourless, pterostigma pale with upper border darkened; metacarp brown (fig.1). Male as females but body smaller with tergite 1 narrower and wings more transparent. Host: unknown, collected from soybeans. Notes: Apanteles gialamensis Long K, sp.n. is related to Apanteles camilla Nixon, 1965, from India, but it differs from the later in the combination of the following features: i). Tergite 1 more narrowed behind (fig. 6), polished and rather smooth; ii). Middle tibia almost black; iii). POL much shorter than OOL and iiii). Propodeum polished smooth. Apanteles gialamensis Long K, sp.n. can be separated from A. typhon Nixon, from South Africa, by the following features: i). Hind tibia black; ii). Ovipositor abruptly curved down at apex and iii). Scutellum with sparse faint punctures. 2. Apanteles subcamilla Long K, sp.n. (fig. 8-13) Material: Holotype, ♀ Apan.036 (IEBR): VN, Hanoi (Gialam), orchard, MT 20O59’N 105O55’E, 15-25.XI.2001, K. D. Long; paratypes 3♀ Apan.037, Apan.038, Apan.041 (IEBR): same locality as holotype, MT 25.XI-05.XII.2001; 2♀ Apan.685, Apan.686 (IEBR): VN, Vinhphuc (Melinh), MT 11-25.X.2000, K. D. Long. Holotype: ♀, length of body 2.6 mm, of fore wing 3.4 mm, of antenna 2.1mm and of setose part of ovipositor sheath 2.1 mm. Head (figs 9, 10): antenna shorter than body (0.8 times as long as body); antennal sockets far above middle line of eyes; eyes weakly convergent below (fig. 10); face width 0.8 times length of face and clypeus combined and 0.9 times height of eye; tentorial pits small, distance between tentorial pits about 2.6 times distance from pit to eye margin; head in dorsal view less transverse (fig. 9), width about 2.0 times as long as median length; ocelli small in low triangle, anterior tangent of the posterior ocelli touching the anterior ocellus (fig. 9); distance between posterior ocelli (POL) 3.5 times diameter of posterior ocellus (Od) and 1.4 times distance from posterior ocellus to eye margin (OOL). Face, apex and occiput polished with fine punctures. Mesosoma: in dorsal view, mesoscutum 1.1 times as wide as width of head; mesoscutum with discrete punctures anteriorly and setose posteriorly. Scutellum almost smooth with sparse shallow punctures; propodeum smooth, spiracles above middle line of propodeum (fig. 11). Wings: fore wing rather long, 1.3 times as long as body; vein r arising behind middle of pterostigma and vein r longer than vein 2-SR, vein 2-SR thicker than vein r, veins r and 2-SR weakly angled (fig. 13); metacarp about 1.2 times as long as pterostigma and 2.9 times as long as its distance from the apex of the radial cell (fig. 13); vein 2-CU1 about 1.2 times as long as vein 1-CU1; vein 1-CU1 1.3 times as long as vein cu-a. Hind wing with cubitellan cell nearly 1.2 times as long as wide. Legs: hind tibia about 0.8 times as long as hind tarsus; inner hind tibial spur 0.5 times as long as hind basitarsus; hind basitarsus 0.45 times as long as hind tarsus; telotarsus shorter than hind fourth tarsus (4: 5). Metasoma: tergite 1 weakly constricted at the middle and weakly narrowed at apex (fig. 12); length of tergite 1 about 1.3 times as long as apical width; median field of tergite 2 strongly transverse and 4.25 times as wide as long; tergite 1 with faint punctures; tergites 2+3 polished, almost smooth. Ovipositor long and straight; hypopygium strongly developed (fig. 8); setose part of ovipositor sheath 0.8 times as long as body. Colour: body polished black; maxillary palpi white except first segment dark brown; labial palpi dark brown; basal two third of fore tibia and tarsus whitish yellow; middle legs black, except middle tibia whitish yellow basally; middle tarsus 1-4 whitish yellow, tarsus 5 brown; hind legs black except basal one third light brown; tibial spurs white; wings hyaline with veins and setae almost colourless, pterostigma pale; metacarpus darkened (fig. 13). Male unknown. Host: unknown, collected from soybeans. Notes: Apanteles subcamilla Long K, sp.n. is closely related to Apanteles camilla Nixon, 1965, from India, but it differs from the later in the combination of the following features: i). Face shiny coriaceous with fine sharp punctures; ii). Ocelli in very low triangle, POL >> OOL (7: 5); iii). Propodeum shiny coriaceous with sparse fine sharp punctures; iiii). Basal median field of tergite 2 smooth. A. subcamilla Long K, sp.n. can be separated from A. gialamensis Long K, sp.n. by the following features: i). Tergite 1 not strongly narrowed apically; ii). Ocelli in a low triangle and POL >> OOL (7: 5); iii). Hypopygium strongly developed and iiii). Median field of tergite 2 strongly transverse.